A situated didactics of the philosophy a model to attend the estrangement of the teachers - Morales, Laura Susana; Belén Bedetti, María (Universidad Pedagógica y Tecnológica de Colombia, 2013)
Training for Philosophy teachers, in the deductive curriculum frames, generates strangeness in those who carry on their internship and their first labor practices, when they come back to school. How to attend this estrangement from a specific didactics of the philosophy without denying the tension among technical, practical and experiential foregrounds? For this, a model denominated as Philosophy’s specific situated didactics is suggested. Such didactics has in its basis, besides the consideration that education is constituted by the tension of the above mentioned foregrounds, a conception of the philosophy referred to as philosophizing Philosophy, which takes into consideration both the subject of the philosophical activity and the disciplinary object, and is opposed to the academism from a perspective that nourishes itself in the situated thought as a philosophic category and in the experience understood as the transformation of subject. That’s why the mentioned didactical model breaks with the explanation, as the university teaching axis, and relies on the narration as the contact point for those involved in the training of trainers and those who begin in Philosophy teaching.